Output tracking control of Boolean control networks with impulsive effects. (27th November 2017) - Xu, Xiaojing; Li, Haitao; Li, Yalu; Alsaadi, Fuad E.
Abstract : This paper studies the output tracking problem of Boolean control networks (BCNs) with impulsive effects via the algebraic state‐space representation approach. The dynamics of BCNs with impulsive effects is converted to an algebraic form. Based on the algebraic form, some necessary and sufficient conditions are presented for the feedback output tracking control of BCNs with impulsive effects. These conditions contain constant reference signal case and time‐varying reference signal case. The study of an illustrative example shows that the obtained new results are effective.